2013
DOI: 10.1021/cg401047a
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal–Organic Hybrid Antifungal Agent: High Level Oriented Assembly of Zinc Hydroxide Carbonate Nanocrystals in Chitosan

Abstract: A novel high level oriented assembly of zinc hydroxide carbonate nanocrystals in chitosan was fabricated via a hydrothermal process. Hydrated chitosan acts as a template supporting and structure-directing reagents for the formation and assembly of zinc hydroxide carbonate nanocrystals. Zinc hydroxide carbonate nanocrystals were heterogeneously nucleated at the interface of hydrated chitosan crystallization regions through hydrogen bonding, lattice geometrical matching, and stereochemical matching interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…33 There was also a small component peak of 535 eV which was ascribed to several associations of oxygen atoms present in the arginine moieties. 39 Arginine being the only source of carbon and nitrogen, the appearance of carbon and nitrogen spectra in the Ag/ZnO HNRs clearly indicates the existence of arginine over the ZnO surface. The high resolution C 1s spectra were deconvoluted into three distinct peaks that correspond to the C-C bond (285.7 eV), and the carbon atoms bonded to different functional moieties of arginine (C-O/C-N at 286.3 eV; and CvO/ O-CvO at 290 eV).…”
Section: Characterizationmentioning
confidence: 96%
“…33 There was also a small component peak of 535 eV which was ascribed to several associations of oxygen atoms present in the arginine moieties. 39 Arginine being the only source of carbon and nitrogen, the appearance of carbon and nitrogen spectra in the Ag/ZnO HNRs clearly indicates the existence of arginine over the ZnO surface. The high resolution C 1s spectra were deconvoluted into three distinct peaks that correspond to the C-C bond (285.7 eV), and the carbon atoms bonded to different functional moieties of arginine (C-O/C-N at 286.3 eV; and CvO/ O-CvO at 290 eV).…”
Section: Characterizationmentioning
confidence: 96%
“…These results suggest that the formation of LZHC in this Zn­(DDAB) 2 -urea system is via a stepwise reaction as follows: Zn­(DDAB) 2 → LZHDC → LZHC. It is noteworthy that the synthesis process occurred via a crystalline and component transformation in this work is significantly different from the classical process that proceeds via a transformation from amorphous phase to promotional crystalline …”
Section: Resultsmentioning
confidence: 93%
“…Usually, the LZHs are obtained via solution methods, including hydrothermal methods mainly performed in basic media such as ammonia, hexamethylenetetramine, and urea. The morphology of LZHs and distance between the brucite-type layers could be varied depending on the kinds of interlamellar species. , As a typical lamellar salt, the layered zinc hydroxide carbonate (LZHC) is composed of zinc hydroxide layers combined with carbonate ions and water molecules. In a typical synthesis process of LZHC, the crystalline evolution proceeds from the amorphous phase to a well-crystallized phase with a nearly invariable distance between the zinc hydroxide layers, and the morphology of LZHC made in these processes is always unitary 2D structure with a disordered stacking of nanosheets. , To obtain uniform LZHC with various unique three-dimensional (3D) morphologies remains a significant challenge. It has been attempted to introduce some surfactants such as CTAB, F127, and P123 as structure-directing agents into the reaction system. However, these agents are often absorbed on the surface of LZHC and therefore fail to bring about the variety of basal spacing due to the unchanged interlamellar anions.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 NPs is useful as protective encapsulating agents that increase adhesive force in the interspecies relation between bacteria and plants (Chowdhury et al 2012;Webster et al 2008). Ruffolo et al (2010) and Song et al (2014) found that ZnTiO 3 and Zn hydroxide carbonate NPs showed higher growth inhibition efficiency of A. niger and fungal activity against cotton Verticillium, Rhizopus, Mucorales than ZnONPs, respectively. Abd-Elsalam (2013) and Mahendra et al (2012) showed that application of NPs grower-friendly in agriculture need to be readily used for protecting crops and avoiding loss to plant pathogens diseases.…”
Section: Introductionmentioning
confidence: 99%